Analisis Kepuasan Pengguna Aplikasi Tiket Pendakian PT MTN Menggunakan Model Delone & McLean - Mochammad Haris Afifudin; Nufan Balafif; Ahmad Farhan (Journal of Innovative and Creativity, 2026)
The purpose of this study is to analyze the influence of system quality, information quality, and service quality on user satisfaction of the Tiket Pendakian Application developed by PT Manggala Teknologi Nusantara (PT MTN), and to identify the most dominant influencing factor. The growing popularity of mountain hiking in Indonesia has driven the digitalization of reservation services through this application, which has been downloaded more than 100,000 times. Despite its convenience, a 3.8 rating and user complaints regarding system speed, information clarity, and transaction issues indicate the need for a comprehensive evaluation of user satisfaction. This study employed a quantitative descriptive–verificative approach using a modified DeLone & McLean (2003) Information System Success Model as the theoretical framework. Primary data were collected using a five-point Likert scale questionnaire distributed to 86 purposively selected users from a population of 592 Google Play Store reviewers. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess the influence of each quality dimension on user satisfaction. The analysis revealed that system quality and service quality have a significant positive effect on user satisfaction, while information quality shows a positive but not significant effect. Collectively, the three variables explain 71.4% of the variance in user satisfaction, with system quality emerging as the most dominant factor influencing satisfaction levels among users. The findings highlight the importance of improving application performance, reliability, and security, as well as strengthening the quality of digital services to enhance user experience. Continuous improvement in these areas is crucial for optimizing PT MTN’s digital mountain reservation services and ensuring long-term user engagement and satisfaction.